2010
DOI: 10.1111/j.1464-410x.2010.09329.x
|View full text |Cite
|
Sign up to set email alerts
|

Risedronate prevents early bone loss and increased bone turnover in the first 6 months of luteinizing hormone‐releasing hormone‐agonist therapy for prostate cancer

Abstract: including 40 men aged ≥ 55 years receiving LHRH-agonist treatment for 6 months for locally advanced prostate cancer. Bone mineral density (BMD) of the lumbar spine, femoral neck, and total hip was measured every 6 months. In addition, bone turnover markers including N-telopeptide, serum C-telopeptide and procollagen peptide, and 25-OH vitamin D and intact parathyroid hormone were measured at baseline and at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 18 publications
0
46
0
4
Order By: Relevance
“…The bone resorption markers N-telopeptide and C-telopeptide increased significantly (21% and 55%, respectively) in this group [54].…”
Section: Clinical Trial Evidencementioning
confidence: 69%
See 1 more Smart Citation
“…The bone resorption markers N-telopeptide and C-telopeptide increased significantly (21% and 55%, respectively) in this group [54].…”
Section: Clinical Trial Evidencementioning
confidence: 69%
“…In a 6-month randomized double-blinded, placebo-controlled trial in 40 men undergoing luteinizing hormonereleasing hormone agonist therapy, Taxel et al [54] evaluated risedronate plus 600 mg calcium and 400 IU vitamin D versus an "identical placebo" plus 600 mg calcium with 400 IU vitamin D. Significant decreases in BMD in the femoral neck (Ϫ2%) and total hip (Ϫ2.2%) and a nonsignificant decrease in BMD in the lumbar spine were observed in the placebo plus calcium and vitamin D (Ca-D) group. The bone resorption markers N-telopeptide and C-telopeptide increased significantly (21% and 55%, respectively) in this group [54].…”
Section: Clinical Trial Evidencementioning
confidence: 99%
“…We included 12 potentially eligible trials and subsequently obtained data for ten of these ( Figure 1). Two trials (Magno et al, 2005;Taxel et al, 2010) including a total of 194 patients were not available because the investigators felt unable to provide the data for inclusion in this metaanalysis. Of the 1017 participants, 512 were randomised to receive bisphosphonates and 505 to placebo or other medical treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The control group was set but not randomized. 7 Taxel et al 18 recently reported the results of a randomized, double-blind, placebo-controlled trial. In their study, 40 men receiving luteinizing hormone-releasing hormone agonist for 6 months for locally advanced PCa were randomized in the risedronate administration group and the control group.…”
Section: Discussionmentioning
confidence: 99%